2019
DOI: 10.1182/blood-2019-121997
|View full text |Cite
|
Sign up to set email alerts
|

Response to Brentuximab Vedotin and Quality of Life in Patients with Relapsed/Refractory Hodgkin Lymphoma (RR HL) in the Real World Setting

Abstract: There is a continued unmet medical need in pts with relapsed/refractory Hodgkin's lymphoma (RR HL). Curing HL pts who have refractory disease after salvage chemotherapy, who relapse after ASCT, or those who are not candidates for ASCT, remains a clinical challenge due to limited effective treatments. There are data available indicating that brentuximab vedotin (BV) brings considerable promise for the treatment of pts with RR HL. Information about BV treatment effectiveness and tolerability both from physician'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Similar results were observed for the CR rate (34% in the clinical trial versus 33.4% in the meta-analysis) [4]. In the pivotal phase II trial, the study population was restricted to patients with an ECOG performance status score of 0 or 1, while some observational studies included patients with ECOG PS 2 or higher [16,24]. Also, patients with previous allogeneic SCT were excluded from the trial, whereas several studies identified in the systematic review included patients with such history of transplantation [14,21,[25][26][27]29,37].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Similar results were observed for the CR rate (34% in the clinical trial versus 33.4% in the meta-analysis) [4]. In the pivotal phase II trial, the study population was restricted to patients with an ECOG performance status score of 0 or 1, while some observational studies included patients with ECOG PS 2 or higher [16,24]. Also, patients with previous allogeneic SCT were excluded from the trial, whereas several studies identified in the systematic review included patients with such history of transplantation [14,21,[25][26][27]29,37].…”
Section: Discussionsupporting
confidence: 65%
“…In these studies, the study populations were representative of patients who are eligible to BV, according to the approved indication. Specifically, the proportion of patients who received previous ASCT ranged from 25.5% [24] to 100% [8,17,36] and 37.5% [27] to 81% [42] patients had refractory HL, defined as stable or progressive disease during first-line or salvage chemotherapy. However, almost half studies (n ¼ 10; 41.7%) did not provide any details regarding the distribution of patients according to relapse or…”
Section: Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation